Environmental controls on coral skeletal δ13C in the northern South China Sea. Issue 4 (1st October 2013) - Deng, Wenfeng; Wei, Gangjian; Xie, Luhua; Yu, Kefu
Abstract [1] In this paper, we investigate the relationship between seasonal climatic and environmental variables, and the skeletal δ13C of modern and mid‐Holocene Porites lutea corals from the southern coast of Hainan Island in the northern South China Sea. No significant correlations were observed between δ13C in the modern coral and solar insolation or sea surface temperature. However, seasonal variability of δ13C in the modern coral covaries with rainfall on Hainan Island. Furthermore, the seasonal variations of δ13C in both the modern and mid‐Holocene coral are synchronous with those of the coral Δδ18O, which is a proxy for seawater δ18O and, in turn, largely controlled by local rainfall. These observations suggest that coral δ13C variations are closely associated with rainfall in this region. Given that river runoff contains dissolved inorganic carbon (DIC) with a negative δ13C, we suggest that periods of high rainfall on Hainan Island deliver increased amounts of 13C‐depleted DIC to coastal seawater, resulting in an enhanced negative δ13C in the corals. Our findings, together with previous studies, appear to demonstrate that in coastal environments, coral skeletal δ13C levels are controlled mainly by terrestrial carbon input and are significantly influenced by terrestrial river runoff. Consequently, the geochemical interpretation of coral δ13C records may differ between coastal areas and offshore areas or the open ocean.